1997
DOI: 10.3109/10731199709118911
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Adhesion Molecules and von Willebrand Factor in Human Coronary Artery Endothelial Cells Incubated with Differently Modified Hemoglobin Solutions

Abstract: Previous studies have established a linkage between free Hb molecules and the production of inflammatory mediators by the reticuloendothelial cells. An important aspect of the endothelial response to the inflammatory stimuli is the expression of adhesion molecules on the luminal surface. Therefore, the present study was designed to investigate the effects of various free-Hb based oxygen carrying solutions on the intracellular adhesion molecule-1 (ICAM-1), the vascular cell adhesion molecule-1 (VCAM-1) and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Several groups have reported that the efficacy of artificial blood substitutes, such as modified hemoglobin solutions, are often hampered by oxidative and inflammatory complications (Simoni et al, 1997;Goldman et al, 1998;Baldwin, 1999). This phenomenon may be related to a difference in heme-releasing capacity of the different hemoglobin solutions.…”
Section: A the Role Of Heme In Inflammationmentioning
confidence: 99%
“…Several groups have reported that the efficacy of artificial blood substitutes, such as modified hemoglobin solutions, are often hampered by oxidative and inflammatory complications (Simoni et al, 1997;Goldman et al, 1998;Baldwin, 1999). This phenomenon may be related to a difference in heme-releasing capacity of the different hemoglobin solutions.…”
Section: A the Role Of Heme In Inflammationmentioning
confidence: 99%
“…Adenosine in HemoTech counteracts vasopressive and pro‐inflammatory properties of Hb by activating adenosine A2A and A2B receptors, which produce vasodilatation, moderation of inflammatory reactions, and prevention of platelet aggregation. Activation of the adenosine A3 receptor provides cytoprotection and induction of adenosine A1 receptor results in neuroprotection (Fig. —center).…”
Section: Methodsmentioning
confidence: 99%
“…GSH also shields heme from reactive oxygen species (ROS) and NO, further lowering the Hb pro-oxidant and vasoconstrictive potential. GSH on the HemoTech surface may form S-nitroso-GSH, thus preventing NO access to heme (15,24,(26)(27)(28)(29)33).…”
Section: Pharmacologic Properties Of Hemotech Moleculementioning
confidence: 99%
See 1 more Smart Citation
“…The disadvantages are that these Hbs are potent oxidizers and activators of redox (NF‐kappa B) and oxygen (HIF‐1) regulated transcription factors . There is an established link between Hb‐mediated oxidative reactions and inflammatory responses . Hb‐induced vasoconstriction via nitric oxide (NO) and non‐NO‐mediated pathways (i.e., ET‐1, RAS, 5‐HT) is also well established .…”
mentioning
confidence: 99%